The Mediating Role of Person Organization Fit in the Effect of Perceived Organizational Support in Nurses Working at a University Hospital on Work Stress - Merve Özlü; Aysun Türe (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: To investigate the mediating role of person-organization fit in the effect of perceived organizational support in nurses on job stress. Method: The sample of the study consisted of 500 nurses working at a university hospital in Eskişehir (N = 923). Data were collected by distributing questionnaires to nurses with the "Personal Information Form", "Perceived Organizational Support Scale", "Perceived Job Stress Scale", and "Person-Organization Fit Scale" and analyzed using SPSS for Windows 25.0 and AMOS 23.0. Results: it was found that the perceived organizational support of nurses significantly affected job stress and person-organization harmony; It was seen that person-organization fit did not affect job stress significantly and person-organization fit did not play a mediating role in the effect of perceived organizational support on job stress. Conclusion: The perceived organizational support variable is important in reducing job stress and increasing person-organization harmony in nurses with professional roles and responsibilities.